Antigens from Rhipicephalus sanguineus ticks elicit potent cell-mediated immune responses in resistant but not in susceptible animals - Ferreira, Beatriz R.; Szabó, Matias J. P.; Cavassani, Karen A.; Bechara, Gervásio H.; Silva, João S. (Elsevier, 2003)
In the present study we compared the immunological reactions between Rhipicephalus sanguineus tick-infested susceptible (dogs and mice) and tick-resistant hosts (guinea pigs), elucidating some of the components of efficient protective responses against ticks. We found that T-cells from guinea pigs infested with adult ticks proliferate vigorously in the presence of concanavalin A (ConA), whereas ConA-induced cell proliferation of tick-infested mice and dogs was significantly decreased at 43.1 and 94.0%, respectively, compared to non-infested controls. Moreover, cells from mice and dogs submitted to one or three successive infestations did not exhibit a T-cell proliferative response to tick antigens, whilst cells from thrice tick-infested guinea pigs, when cultured with either a tick extract or tick saliva, displayed a significant increase in cell proliferation. Also, we evaluated the response of tick-infested mice to a cutaneous hypersensitivity test induced by a tick extract. Tick-infested mice developed a significant immediate reaction, whereby a 29.9% increase in the footpad thickness was observed. No delayed-type hypersensitivity (DTH) reaction was detected. Finally, the differential cell count at the tick attachment site in repeatedly infested mice exhibited a 6.6- and 4.1-fold increase in the percentage of eosinophils and neutrophils, respectively, compared to non-infested animals, while a decrease of 77.0-40.9 in the percentage of mononuclear cells was observed. The results of the cutaneous hypersensitivity test and the cellular counts at the tick feeding site for mice support the view that tick-infested mice develop an immune response to R. sanguineus ticks very similar to dogs, the natural host of this species of tick, but very different from guinea pigs (resistant host), which develop a DTH reaction in addition to a basophil and mononuclear cell infiltration at the tick-attachment site. In conclusion, saliva introduced during tick infestations reduces the ability of a susceptible animal host to respond to tick antigens that could stimulate a protective immune response. As a consequence, the animals present a lack of DTH response and disturbed cellular migration to tick feeding site, which can represent a deficient response against ticks. © 2003 Elsevier B.V. All rights reserved.
Keywords: Cellular immunity; Dog; Hypersensitivity; Immune response; Mice model; Rhipicephalus sanguineus; animal experiment; cell count; cell infiltration; cell proliferation; cellular immunity; controlled study; dog; eosinophil; female; guinea pig; infection resistance; infection sensitivity; mononuclear cell; mouse; neutrophil; nonhuman; saliva; skin allergy; skin test; T lymphocyte; tick; Animals; Antigens; Cell Division; Concanavalin A; Disease Susceptibility; Dog Diseases; Dogs; Female; Guinea Pigs; Host-Parasite Relations; Ixodidae; Male; Mice; Mice, Inbred C3H; Saliva; Skin; T-Lymphocytes; Tick Infestations; Acari; Animalia; Canis familiaris; Cavia; Rhipicephalus